METHODS AND TECHNIQUES OF USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN FOREIGN LANGUAGE LESSONS - Rashidova , Munavvar Xaydarovna; Namozova , Dilnoza Berdimurotovna (Innovative Development in Educational Activities, 2024)
The article explores the effectiveness of using information and communication technologies in foreign language lessons. It also analyzes the peculiarities of learning a foreign language and the relevance of applying a computer in the classroom.